2011
DOI: 10.1007/s12032-011-9850-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HER2 gene amplification and protein expression in esophageal squamous cell carcinoma

Abstract: The HER2 gene, which is located on chromosomes 17, is a therapeutic target for cancer. Amplification of HER2 has been described in several tumor types. However, few studies of HER2 gene amplification and protein expression in esophageal carcinoma have been conducted. This study was to investigate the relationship between the expression of HER2/neu and the clinical characteristics, including survival rate, of esophageal squamous carcinoma. The clinical data of 145 patients admitted in Renmin Hospital of Wuhan U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 32 publications
2
38
3
Order By: Relevance
“…However, another study by the same authors found that HER2 heterogeneity among HER2 amplified EACs was an independent predictor of worse cancer-specific survival [41]. Apart from EAC, HER2 overexpression was also found to be a negative predictor of survival in esophageal squamous cell carcinoma [42]. …”
Section: Her2 Overexpression In Cancersmentioning
confidence: 99%
“…However, another study by the same authors found that HER2 heterogeneity among HER2 amplified EACs was an independent predictor of worse cancer-specific survival [41]. Apart from EAC, HER2 overexpression was also found to be a negative predictor of survival in esophageal squamous cell carcinoma [42]. …”
Section: Her2 Overexpression In Cancersmentioning
confidence: 99%
“…We found a significant negative correlation between overexpression of HER-2/neu and tumor differentiation which means HER-2/neu overexpression was more common in poorly differentiated ESCC (high grade tumors) versus other grades. A recent study also reported a significant correlation between the overexpression of HER2/neu and the differentiation of the esophageal squamous cell carcinoma (30). In contrast, Raziei et al (6) found that well differentiated tumors overexpress the HER-2/neu protein in patients with gastric cancer.…”
mentioning
confidence: 96%
“…clinicopathological features of patients with ESCC were investigated in the present study. In previous studies, the number of copies of the HER2/neu gene was analyzed by fluorescence or chromogenic in situ hybridization, and the protein expression levels of HER2 were evaluated by IHC (6,7,9,10,12,(16)(17)(18)(19). Previous studies examining the association between the expression levels of HER2 (as determined by IHC) and prognosis in patients with ESCC have reported conflicting results (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed that the oncogene HER2/neu was overexpressed in 2.0-19.1% cases of ESCC (6)(7)(8)(9)(10)(11)(12)(13), and increased protein expression levels of HER2 have been previously observed in EC (14,15) and ESCC (6,7). However, the role of HER2 in ESCC remains controversial (6,7,9,10,12,(16)(17)(18)(19). Multidrug resistance protein 1 (MRP1), as a member of the adenosine triphosphate-binding cassette transporter family, has been implicated in resistance to cancer therapeutics (20).…”
Section: Introductionmentioning
confidence: 99%